Green entrepreneurship intention in university students: the case of Peru - Alvarez-Risco, Aldo (2021)
Objective: The aim is to better understand how education supports green entrepreneurship among students by analyzing their education development support, institutional support, country support, and entrepreneurial self-efficacy. Research Design & Methods: A total of 320 international business students in Peru filled the online survey. Eight questions focused on demographic information, and twenty-six questions evaluated the green entrepreneurship intention of students. We used the SEM-PLS technical analysis. Findings: We found that education development support (EDS; 0.146), institutional support (IS; 0.183), and country support (CS; 0.158) had a positive influence on entrepreneurial self-efficacy (ESE), while ESE had a positive influence (0.757) on the green entrepreneurial intention (GEI). The model explained 57.3% of the green entrepreneurial intention. Findings of the bootstrapping test showed that the path coefficients were significant. Implications & Recommendations: This study showed the impact of education development support, institutional support, and country support on entrepreneurs’ ability to successfully carry out green entrepreneurship, which will serve universities to implement strategic plans to achieve their ecological ventures and develop such ventures on campus with the students that have the necessary skills. Contribution & Value Added: The research findings will prove helpful to governments in establishing new norms to promote entrepreneurship. The novelty of the current study is supported in using the PLS-SEM technique.